Voluntary versus enforced tax compliance: Empirical evidence from digital-based freelancer - Mardiyah, Aynun; Salmavira, Alisa; Inasius, Fany (Edelweiss Applied Science and Technology, 2025)
The Slippery Slope Framework demonstrates that tax compliance behavior is influenced by the dimensions of trust and power within the relationship between taxpayers and the government. Although the framework has been tested by numerous empirical studies, there remains a lack of research focusing on shadow economy actors. Therefore, this study aims to examine the existence of these dimensions and their influence on the perception of tax compliance among digital-based freelancers in Indonesia. A total of 408 digital freelancers participated in an online questionnaire survey, and the data were analyzed using a stepwise linear regression model. The results indicated that perceived government power was positively correlated with approval of voluntary tax compliance. However, the study did not find a significant effect of perceived government power or trust in government on enforced tax compliance. The Slippery Slope Framework is only partially supported by these data. The purpose of this study is to contribute to the existing body of knowledge regarding the impact of power and trust on voluntary and enforced tax compliance in developing countries dealing with a shadow economy, particularly in Asia.